Atrial fibrillation management in Asia: From the Asian expert forum on atrial fibrillation - Chiang, Chern-En; Zhang, Shu; Tse, Hung Fat; Teo, Wee Siong; Omar, Razali; Sriratanasathavorn, Charn (International journal of cardiology, 2013)
Atrial fibrillation (AF), the most common sustained cardiac arrhythmia, is associated with increased morbidity and mortality. AF has a slightly lower incidence and prevalence in Asian populations than in Western populations, but the associated relative risk of stroke and mortality is similar. Patients with AF in Asia have similar disease profiles and CHADS2 score distributions compared to those in the West, with the exception of a slightly higher prevalence of valvular heart diseases in Asia. Acute ventricular rate control should be the initial consideration in patients with AF and rapid ventricular rate. Anti-arrhythmic drugs have only a modest long-term effect on maintenance of sinus rhythm, and clinical trials in both the West and the East show that chronic rhythm control is not superior to chronic rate control in terms of cardiovascular outcomes, most likely because the benefit of anti-arrhythmic drugs in these trials was often offset by proarrhythmic effects. ECG-driven trials for AF should be replaced by outcome-driven ones. ATHENA is the largest outcome trial to confirm the superiority of a new anti-arrhythmic drug in improving cardiovascular outcomes. The choice of anti-arrhythmic drugs for AF should be based on both safety and efficacy in improving cardiovascular outcomes. For long-term rate control, a lenient strategy with a ventricular rate of less than 110bpm may be adequate, but more strict rate control may be required if patients continue to complain of symptoms. Catheter ablation should be reserved for patients who remain symptomatic despite optimal medical therapy.